The Relationship between Bank Capital, Risk-Taking, and Capital Regulation: A Review of the Literature - Stéphanie Stolz (Kiel Institute of World Economics (IfW), 2002)
Bank capital regulation seems to be today's most accepted regulatory instrument. The reasoning is that limited liability and deposit insurance appear to give banks incentives for excessive risk-taking. Capital requirements can alleviate this problem as banks are obliged to hold more capital which forces them to have more of their own funds at risk. But the theoretical literature has much more to say on how banks determine their capital structure and portfolio risk and how capital regulation influences this decision. This paper attempts to give an overview of the literature in order to see what theory suggests, what empirics seem to tell us, and what there is still to do for future research.
Keywords: G2; 330; Banking regulation; deposit insurance; capital structure; Eigenkapitalvorschriften; Bankbilanz; Kapitalstruktur; Bankrisiko; Portfolio-Management; Einlagensicherung; Theorie; Welt